Cemaran Bakteri Gram Negatif pada Jajanan Siomay di Kota Kendari - Reni Yunus; Ruth Mongan; Rosnani Rosnani (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2017)
Foodborne disease caused by food infection is one of health concern which cause of consumption of contaminated foods that containing living microorganisms. There are several kinds of microorganisms that can cause food infection, one of them is Salmonella sp, a negative Gram basil shaped-bacteria as the cause typhoid and paratyphoid diseases. The purpose of this study is isolate and identify negative Gram bacteria on snacks in the traditional market Anduonuhu Kendari. This research is a descriptive study with dumplings samples which sale on the traditional Market Anduonohu as population. Samples were taken as a total sampling with pour plate method was used for bacterial isolation. All 10 samples were shown positive result which growth in Brain Heart Infusion Broth media as 7 of them are positively grow in Salmonella Shigella Agar with negative Gram basil-shaped bacteria was found under the microscope after Gram staining, suspected as negative Gram baceria. It can be concluded that 7 (70%) out of of 10 dumplings samples were contaminated negative Gram bacteria. This research can be continued by identifying other pathogenic bacteria which are the bacteria that cause food borne disease.